2011
DOI: 10.1155/2011/904132
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Anomalies around The Wenchuan Earthquake and Their Relationship with Earthquake Preparation

Abstract: Electromagnetic precursors before the Wenchuan earthquake on May 12, 2008 were collected and summarized on the basis of related published papers. The relationship between electromagnetic anomalies and different earthquake preparation stages was analyzed, and an entire seismic preparation process was constructed according to corresponding anomalies in different electromagnetic parameters. It is illustrated that stereo electromagnetic observation is useful in the understanding of earthquake preparation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The number of pre-earthquake thermal, surface latent heat flux and outgoing longwave radiation anomalies apparently results from earthquake-related gas emission from the lithosphere (Tronin et al, 2002;Dey et al, 2004;Tronin, 2006;Ouzounov et al, 2007;Tramutoli et al, 2013). Thermal (Zhang et al, 2010), ionospheric (Lin, 2012(Lin, , 2013Zhu et al, 2010), electromagnetic (Zhang et al, 2012) and aerosol (Qin et al, 2014) anomalies were found before the Wenchuan earthquake of 12 May 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The number of pre-earthquake thermal, surface latent heat flux and outgoing longwave radiation anomalies apparently results from earthquake-related gas emission from the lithosphere (Tronin et al, 2002;Dey et al, 2004;Tronin, 2006;Ouzounov et al, 2007;Tramutoli et al, 2013). Thermal (Zhang et al, 2010), ionospheric (Lin, 2012(Lin, , 2013Zhu et al, 2010), electromagnetic (Zhang et al, 2012) and aerosol (Qin et al, 2014) anomalies were found before the Wenchuan earthquake of 12 May 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The number of pre-earthquake thermal, surface latent heat flux and outgoing longwave radiation anomalies apparently results from earthquakerelated gas emission from the lithosphere (Tronin et al, 2002;Dey et al, 2004;Tronin, 2006;Ouzounov et al, 2007). Thermal (Zhang et al, 2010), ionospheric (Lin, 2012(Lin, , 2013Zhu et al, 2010), electromagnetic (Zhang et al, 2011a), and aerosol (Qin et al, 2014) anomalies were found before the Wenchuan earthquake of May 12, 2008. As the second most important greenhouse gas after carbon dioxide (CO 2 ), methane (CH 4 ) is approximately 20 times better at warming the atmosphere than CO 2 by weight and plays an important role in atmospheric chemistry. Some people have speculated that thermal abnormalities before earthquakes are related to the release of CH 4 .…”
mentioning
confidence: 99%
“…This stereo seismo-electromagnetic monitoring system will provide strong support for understanding the formation, propagation, and coupling processes of electromagnetic signals from lithosphere to atmosphere and ionosphere during earthquake preparation and occurrence. By combining the multi-parameters together from ground to the ionosphere, the earthquake preparation process can be built up not only in temporal frame, but in spatial distributions due to their different sensitivity to the physical properties of media in the Earth's spheres (Zhang and Shen 2011;Zhang et al 2016). The development in new technologies and data processing methods on seismo-electromagnetics exhibited in EMSEV 2016 is quite inspiring.…”
mentioning
confidence: 99%